Certification Compliant Performance Analysis and Requirements Management of an Electrically Powered General Aviation Aircraft - Hein, Luca; Panchal, Purav; Myschik, Stephan (2023 10th International Conference on Recent Advances in Air and Space Technologies (RAST), 2023)
This paper presents an implementation of a requirements validation toolchain for certification compliant aircraft performance analysis of an electrically powered general aviation aircraft. As part of the dtec.bw project ELAPSED, a novel electric propulsion system approach for a CS-22 class aircraft is being developed. In order to comply with CS-22 certification rules, pre-defined aircraft requirements must be fulfilled by the design, such as a maximum take-off distance of 500 m. To validate the feasibility of aircraft and system requirements and their accordance with the certification standards, a toolchain providing bidirectional traceability from requirements to test results has been set up. This toolchain is comprised of Polarion PLM for requirements management and MATLAB/Simulink providing mission evaluation capabilities using a nonlinear simulation model of the specific aircraft. Two inhouse tools named SimPol and Tico provide connectivity and round-tripping between Polarion and Simulink. Application of this toolchain is presented along a test run of 3 requirements.